Successful Young Athletes Have Low Probability of Being Ranked Among the Best Senior Athletes, but This Is Higher When Compared to Their Less Successful Peers - Bezuglov, Eduard; Emanov, Anton; Waśkiewicz, Zbigniew; Semeniuk, Nadezhda; Butovsky, Mikhail; Shoshorina, Maria; Baranova, Daria; Volodina, Kristina; Morgans, Ryland (Frontiers in Psychology, 2022)
Background: Contemporary research has shown that only a small proportion of high achieving young athletes continue to become successful senior athletes. However, there is a lack of empirical literature tracking the success of senior male and female athletes who were considered high achieving as a youth. Hypothesis: Athletes of both sexes who are successful in youth categories (U18 and U20) are more likely to be successful senior athletes. Data from 67,600 athletes were collated from the tilastopaja.org platform. The inclusion criteria for both genders were determined by top-100 ranking in the U18 and U20 age groups and progression to the top-100 as a senior athlete. Only 23.5% of successful track and field athletes (ranked in top-100) at U18 became a successful senior athlete, while 35.4% were from the U20 group. Girls ranked in the top-100 U18 and U20 categories are significantly more likely to be ranked in the top-100 as a senior when compared to boys. Although, being ranked in the top-50 at U18 and U20 significantly increases the probability of becoming a successful senior athlete when compared with less successful athletes at these age groups (p <0.001). Notably, the majority (68.5%) of the most successful senior athletes were not ranked in the top-100 when in the U18 or U20 age groups. Only a small group of track and field athletes that are successful at U18 and U20 become successful at senior level. The most successful track and field youth athletes are significantly more likely to succeed as a senior athlete than their less successful peers, while girls are more likely to be successful than boys.